Chemical synthesis and applications of graphene and carbon materials - Antonietti, M.; Müllen, K. (Engineering professional collection, 2017)
This ready reference and handbook is unique in focusing on synthesis and the application of graphene and other carbon materials with an emphasis on chemistry aspects. It deals with top-down and bottom-up approaches, and presents the best synthetic methods.